0

# How do you find the equation to an integral when the equation is not given but the answer to the integral is?

int; integral sign

Find int (bottom: -3 top: -5.5) (8*f(x)-9)dx when int (bottom:-5.5 top:-3) f(x)dx = -2

Also; let

int (bottom: -8 top: -0.5) f(x)dx =8

int (bottom: -8 top: -5.5) f(x)dx = 9

int (bottom: -3 top: -0.5) f(x)dx = 1

### 2 Answers by Expert Tutors

Howard L. | Experienced Math Tutor Specializing in Test Prep & Grade Up SkillsExperienced Math Tutor Specializing in T...
5.0 5.0 (21 lesson ratings) (21)
0

The integral of 8f(x)-9 has two parts of area, say A1= 8f(x) defined by variable x and A2= -9 defined by constant number -9.  We take integral to get the area from -3 to -5.5 by changing the up-down bound order from -5.5 to -3 and the sign + to -.  Then, proceed all the rest as,

Q1:    Area from -3 to -5.5

\int_{-3}^{-5.5} ( 8f(x) - 9) dx

= -\int_{-5.5}^{-3} ( 8 f(x) - 9) dx

= -8 \int_{-5.5}^{-3} f(x) dx + 9 \int_ {-5.5}^{-3} dx

= (-8)(-2) + 9 \int_{-5.5}^{-3} dx

=-16 + 9x|_{-5.5}^{-3}

=16 + (-27-(-49.5))

=16 + 22.5  ( A1+  A2)

=38.5

Q2:  Area from -8 to -0.5

Variable area A1= 8f(x) = 8*8=64;

Fixed area A= -9x|_{-8}^{-0.5}= -9 (-0.5-(-8))= -67.5

Total area A = A1 + A= -3.5

Q3:  Area from -8 to -5.5

A = 8*9 =72;    A= -9x|_{-8}^{-5.5}= -9 (-5.5-(-8)) = -22.5:

A  = A1 + A2 = 49.5

Q4:   Area from -3 to -0.5

A1 = 8*1 = 8;       A2 = -9( -0.5 - ( -3))= -22.5

A = -14.5

Proof:  Q2 = -Q1 + Q3 + Q4    (Q1 is negative because of up-down bound change)

-3.5 = -38.5 + 49.5 - 14.5

George C. | Humboldt State and Georgetown graduateHumboldt State and Georgetown graduate
5.0 5.0 (2 lesson ratings) (2)
0

This is more a linear algebra problem than a calculus problem.  Set up a matrix from your given information.

Let f(-.5)=a. f(-8)=b, f(5.5)=c, f(-3)=d

From a plot, these are not a straight line.  Their arrangement resembles a cubic function.  Thus the equation  ax^3 + bx^2 + cx + d  will be the form.  Using the coefficients as the unknowns and the values of x as the coefficients, the matrix becomes

a           -b                                                     =8

-b               +c                                  =9

a                                              -d                  =1

-c             +d                  =2

-.125               .25                -.5                 1               8

-512                 64                -8                  1               9

-166.375           30.25           -5.5                1               1

-27                   9                  -3                  1              -2

Huffing and puffing gives

f(x) =  .0853 x^3  +  1.808 x^2  +  9.4107 x  +  12.264

f'x)= .2559 x^2  +  3.6160 x  +  9.4107